2023
DOI: 10.2147/ccid.s422928
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Drug-Induced Severe Cutaneous Adverse Reaction Epidermal Necrolysis (EN): An Analysis Using FDA Adverse Event Reporting System (FAERS) Database

Weiqiang Fei,
Jun Shen,
Hui Cai

Abstract: Purpose The purpose of the study is to analyze FAERS data to identify drugs associated with Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN), determine demographics, drug classes involved, most likely resulted in death, and highlight emerging trends in SJS/TEN reactions. Patients and Methods We reviewed the publicly available FAERS database from 2004–2021. Using search terms “Stevens-Johnson syndrome” or “Toxic epidermal necrolysis”, we identified the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A retrospective analysis of 59 TEN cases reported in Yokohama City University Hospital and Yokohama City University Medical Center between January 2000 and March 2020 revealed a mortality rate of 13.6% ( n = 8) [ 42 ]. Higher rates of SJS/TEN mortality were demonstrated in the USA: for the period from 2004 to 2021 there were 24,976 cases of SJS/TEN in the Food and Drug Administration Adverse Event Reporting System (FAERS) database, and 19.53% were fatal [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A retrospective analysis of 59 TEN cases reported in Yokohama City University Hospital and Yokohama City University Medical Center between January 2000 and March 2020 revealed a mortality rate of 13.6% ( n = 8) [ 42 ]. Higher rates of SJS/TEN mortality were demonstrated in the USA: for the period from 2004 to 2021 there were 24,976 cases of SJS/TEN in the Food and Drug Administration Adverse Event Reporting System (FAERS) database, and 19.53% were fatal [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antiepileptics are well-known causes of SJS and TEN. They accounted for up to 19.37% of all SJS and TEN reports retrieved from the FAERS database from 2004 to 2021 [ 43 ]. There are a lot of studies identifying the high risk of SJS and TEN associated with antiepileptics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on data from the FDA Adverse Event Reporting System (FAERS) between 2004 and 2021, AEDs belonged to the major drug classes that cause Stevens-Johnson syndrome (SJS)/Toxic epidermal necrolysis (TEN), and 19.37% of all reports were related to AEDs. Specifically, phenytoin was identified as the most frequently reported drug [30]. The study analyzing 2,942 cases of drug eruption from KAERS DB between 2008 to 2017 found that lamotrigine, valproate, carbamazepine, oxcarbazepine, levetiracetam, and phenytoin were the cause of the eruptions [31].…”
Section: Discussionmentioning
confidence: 99%